Transparansi Dana Penanggulangan Bencana Covid-19 di Kabupaten Gianyar - Ida Ayu Rysma Dewi; Nyoman Ari Surya Darmawan (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
This study aimed at investigating the transparency of Coronavirus disaster relief fund in Gianyar district. Principles of transparency were used in this study as the variables that refers to (Andrianto, 2007) . Quantitative method was used in this study with the population of 64 villages and 6 urban villages from 7 sub-districs in Gianyar district. The samples of this study were 120 participants who were selected by using purposive sampling. Primary data was used and the data were collected by using Google Form that is measured by using Five-point Likert Scale. SPSS 20 was used in this study to analyze the multiple linear analysis. The results of this study showed that. The transparency of Coronavirus disaster relief fund in Gianyar district is not conducted optimally. This is showed by the management of village funds that have not fully implemented the principle of transparency. Therefore, the management of village funds in Gianyar only can be said as transparent.